PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA PADA KECELAKAAN (FIRST AID) PADA SISWA/SISWA SMA KAMPAR RIAU - Putri Wulan Dini S (Jurnal Pengabdian Masyarakat Multidisiplin, 2017)
First Aid is a temporary relief and care effort against accident victims before getting more complete help from doctors or paramedics. This means that the help is not a perfect treatment or treatment, but only a temporary relief by the FIRST AID officer (medical officer or lay person) who first sees the victim. First Aid Purpose: 1 Prevent death, 2. Prevent more severe disability 3. Prevent infections, 4. Reduce pain and fear Correct FIRST AID action will reduce defects or suffering and even save the victim from death, but if FIRST AID action is done bad it can worsen due to accident and even kill the victim. In everyday life there is often an accident that befell someone or a group of people. Accidents can happen anywhere, at home, road, workplace or anywhere else. To anticipate the problem then the government launched the school health effort movement (UKS) which there is health education, health services and a healthy school environment. The purpose of this dedication is to train the students to be the first helpers to be able to perform first aid measures if necessary.